Anatomy of a conflict identity, knowledge, and emotion in old-growth forests - Satterfield, Terre, 1960-; ebrary, Inc. (Vancouver : UBC Press ; East Lansing, Mich. : Michigan State University Press, 2002)
"Anatomy of a Conflict explores the cultural aspects of the fierce dispute between activist loggers and environmentalists over the fate of Oregon's temperate rain forest. Centred on the practice of old-growth logging and the survival of the northern spotted owl, the conflict has led to the burning down of ranger stations, the spiking of trees, blockades of logging trucks, and countless demonstrations and arrests."--BOOK JACKET.
Includes bibliographical references.
Electronic reproduction.
Keywords: Old growth forests -- Oregon; Old growth forest conservation -- Oregon; Old growth forest ecology -- Oregon; Logging -- Oregon; Environmentalists -- Oregon -- Attitudes; Loggers -- Oregon -- Attitudes; Electronic books